Outcomes of patients presenting with acute coronary syndromes on workdays vs. rest days (SPUM-ACS substudy). (3rd October 2022) - Matter, M; Candreva, A; Stahli, B E; Klingenberg, R; Raber, L; Windecker, S; Rodondi, N; Nanchen, D; Mach, F; Gencer, B; Ruschitzka, F; Luscher, T F; et al.
Abstract: Introduction: Conflicting data exist upon whether patients presenting with acute coronary syndromes (ACS) during on- or off-hours differ regarding outcomes. Moreover, definitions of on- and off-hours vary in literature. The notion of a weekend effect with increased mortality has been raised, mostly seen in relation to lesser use of invasive treatment. Purpose: This multi-center study investigated the baseline characteristics and associated outcomes of patients presenting with ACS undergoing coronary angiography on weekdays compared to those presenting on weekends or holidays. Methods: Data from the prospective SPUM-ACS (Special Program University Medicine Acute Coronary Syndromes and Inflammation) Cohort were examined, with patients recruited between 2009 and 2012. Patients were divided into two groups according to whether they presented for coronary angiography for ACS on workdays (Monday-Friday, 00:00–23:59) or on rest days (Saturday or Sunday, 00:00–23:59, and public holidays shared by all centers). Time of presentation was defined as time point of catheter sheath insertion. Results: From a total of 2168 patients (21.4% females), 1828 (84.3%) presented on workdays, 340 (15.7%) on rest days without difference in female/male ratio. On rest days, patients more often showed signs of advanced heart failure (Killip Class III–IV 3.9% vs. 7.1%, p=0.009). Patients presented more frequently with ST-segment elevation ACS (STE-ACS) than non-ST-segment elevation ACS (STE-ACS on workdays vs. rest days: 50.4% vs. 65.0%, p<0.001). In- and out-of-hospital time delay metrics did not differ between groups, apart from symptom onset-to-balloon time, which was shorter on rest days (598 vs. 520 min, p=0.040). There was a trend towards more frequent use of percutaneous (89.2% vs. 92.6%, p=0.053) or surgical (3.3% vs 5.0%, p=0.131) revascularization on rest days. 30-day all-cause mortality was higher on rest days for any ACS (1.75% vs 3.82%, p=0.007) and for STE-ACS only (2.39% vs 4.98%, p=0.019, Fig. 1). Notably, the same trend was seen when comparing only patients presenting with Killip Class III/IV, both for any ACS (11.27% vs. 20.83%, p=0.119) and for STE-ACS (14.00% vs. 26.32%, p=0.114). On rest days, female patients showed higher 30-day all-cause mortality than males for any ACS (7.46% vs 2.93%, p=0.042); the same trend was observed for STE-ACS (8.89% vs. 3.98%, p=0.088). Conclusions: On rest days, patients more often presented with STE-ACS and more frequently showed signs of advanced heart failure, with similar use of invasive revascularization as for patients presenting on workdays. This might contribute to higher early mortality observed in ACS patients on rest days. These differences persisted within the subgroups STE-ACS and Killip Class III/IV. Interestingly, female patients showed increased early mortality on rest days compared to males. Thus, patients presenting with ACS on rest days warrant particular attention. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation (SNSF)